Clinical applications of ketamine: a literature review - Kaptur, Agata; Dziedziński, Dawid; Łoś, Dawid; Nowak, Aleksandra; Janus, Anita; Kwaśniewska, Oliwia (Quality in Sport, 2024)
Ketamine, initially recognized for its anesthetic capabilities, has emerged as a multifaceted pharmacological intervention with applications extending beyond the surgical setting. This literature review explores the diverse clinical applications of ketamine, delving into its well-established role in anesthesiology and its burgeoning potential in the psychiatric domain. The review discusses ketamine's mechanism of action, emphasizing its unique profile as an NMDA receptor antagonist. Its rapid-acting antidepressant and anti-suicidal effects are highlighted, along with its efficacy in treating conditions like treatment-resistant depression and post-traumatic stress disorder. Additionally, the review examines ketamine's utility in pain management, particularly for acute and chronic pain syndromes. This comprehensive assessment underscores ketamine's evolving role as a valuable tool in both anesthesiology and psychiatry. Materials and methods A comprehensive review of the scientific literature was conducted by thoroughly searching the PubMed database to closely examine the most recent findings on the various clinical applications of ketamine. The search was carefully restricted to only include articles published within the last 10 years, with a focus on those that were indexed in PubMed, written in English, and categorized as high-quality meta-analyses, original research studies, clinical trials, or comprehensive review articles. In order to ensure the most relevant and reliable information was gathered, case reports and non-English language articles were excluded from consideration. The key terms used for searching the database encompassed the broad range of ketamine's clinical uses, including "ketamine," "anesthesia," "critical care," "psychiatry," "depression," and "pain."